Indoor Air Quality Index–Based Assessment and Improvement Strategies for Selected Kindergarten Classrooms in Pagoh, Johor - Huril Ain Asrin; Mohd Syafiq Syazwan Mustafa; Azian Hariri; Abdul Murad Zainal Abidin; Hamzah Hajono; Maranatha Wijayaningtyas; Amir Abdullah Muhamad Damanhuri (Journal of Advanced Industrial Technology and Application, 2026)
Indoor air quality (IAQ) in kindergarten classrooms is critical due to children’s vulnerability to environmental pollutants and thermal discomfort. This study assessed IAQ conditions and determined the Indoor Air Quality Index (IAQI) status of two private kindergartens in Pagoh, Johor namely S1 and S2, using a quantitative field measurement–based approach. Temperature, relative humidity, CO₂, TVOC, PM₂.₅, and PM₁₀ were monitored over two school days and evaluated against Department of Occupational Safety and Health (DOSH) and Singapore Standard (SS 554) guidelines, and IAQI values were calculated using linear interpolation, where the lowest IAQI value represented the overall indoor air quality status. The results showed that chemical pollutants generally complied with the recommended limits; however, dominant parameters affecting IAQ differed between the two kindergartens. S1 was classified as Unhealthy due to elevated temperature (34.5℃) and RH (87%), with IAQI values of 39.1 and 42.7, respectively.  In contrast, S2 was classified as Hazardous due to high CO₂ concentrations (2755 ppm) associated with limited ventilation which recorded a critically low IAQI value of 9.0. These findings highlight the need for improved ventilation and thermal management in kindergarten classrooms.